2022
DOI: 10.5603/cj.a2020.0073
|View full text |Cite
|
Sign up to set email alerts
|

Complexity assessment and technical aspect of coronary angiogram and percutaneous coronary intervention following transcatheter aortic valve implantation

Abstract: Background Performing selective coronary angiogram (CA) and percutaneous coronary intervention (PCI) post transcatheter aortic valve implantation (TAVI) may be challenging with various success rates of coronary ostia engagement. Methods Among all patients who underwent CA and/or PCI after TAVI from our single center TAVI registry, ostia cannulation success was reported according to the quality of ostia engagement and artery opacification, and was classified as either se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…A higher residual SS after PCI before or during TAVI had a significant impact on the primary endpoint (14). In contrast, Paradis et al found no difference in the composite endpoint of all-cause mortality, myocardial infarction, and stroke after 30 days or 1 year between CAD patients stratified according to low (≤22), intermediate (21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and high (≥33) SS and patients without CAD undergoing TAVI (13). Finally, the largest study with a multicenter design included 1,270 patients who were stratified into three groups according to their pre-TAVI status: no CAD, non-severe CAD (SS < 22), or severe CAD (SS ≥ 22); those undergoing PCI were further subdivided into "reasonably" incomplete revascularization with a residual SS < 8 and "incomplete" revascularization with a rSS of >8 (31).…”
Section: Coronary Artery Disease and Pci: The Dilemma Of The Prognostic Role In Tavi Patientsmentioning
confidence: 93%
See 2 more Smart Citations
“…A higher residual SS after PCI before or during TAVI had a significant impact on the primary endpoint (14). In contrast, Paradis et al found no difference in the composite endpoint of all-cause mortality, myocardial infarction, and stroke after 30 days or 1 year between CAD patients stratified according to low (≤22), intermediate (21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and high (≥33) SS and patients without CAD undergoing TAVI (13). Finally, the largest study with a multicenter design included 1,270 patients who were stratified into three groups according to their pre-TAVI status: no CAD, non-severe CAD (SS < 22), or severe CAD (SS ≥ 22); those undergoing PCI were further subdivided into "reasonably" incomplete revascularization with a residual SS < 8 and "incomplete" revascularization with a rSS of >8 (31).…”
Section: Coronary Artery Disease and Pci: The Dilemma Of The Prognostic Role In Tavi Patientsmentioning
confidence: 93%
“…To date, little data exists on the incidence of CA and/or PCI after TAVI outside the periprocedural setting, as a result of ACS, CCS, or other reasons, particularly with respect to long-term follow-up. In the mostly single-center studies available in the literature, the incidence of CA in TAVI patients ranges between 2.5 and 5.3%, with PCI performed in 27–55% of cases ( 28 30 , 33 35 ) ( Table 2 ). According to Nai Fovino et al, the frequency of CA post-TAVI during a follow-up period of 2.1 years was 5.3% in a single-center cohort comprising 912 patients ( 30 ).…”
Section: Management Of Coronary Angiography and Pci After Tavimentioning
confidence: 99%
See 1 more Smart Citation
“…Post-TAVI PCI can be challenging depending on the type of valve. 8 The self-expanding valves covering the coronary ostia may require more skill to re-access the coronary ostium. Commissure alignment technique may partially reduce the technical challenges.…”
Section: See Article By Chavarría Et Al Pages 23e30 Of This Issuementioning
confidence: 99%
“…A total of 6252 patients were included. Five studies were conducted in the USA (Jeroudi et al, 2018;Guedeney et al, 2019;Abugroun et al, 2020;Ghrair et al, 2020;Tran et al, 2022), two in Switzerland (Winter et al, 2021;Perrin et al, 2022), two in France (Denimal et al, 2021;Matta et al, 2021), one in Japan (Kaihara et al, 2021), and one in Canada (Ferreira-Neto et al, 2019). Table 2 presents the characteristics of the included studies.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%